Psychometric assessment of patients with congestive heart failure by using hospital anxiety and depression scale - Nadhrati Surura, Hedya; Al Bukhari, Al Bukhari; Bellari Putri, Dizi; Khairul Fikri, Handy; Maulida Ulfa, Neily (International Journal of Public Health Science (IJPHS), 2024)
Congestive heart failure (CHF) is a progressive health problem that has increased morbidity and mortality. However, studies on validating measures of anxiety and depression symptoms of CHF patients are still limited. The observational study enrolled 53 CHF patients who visited the Internal Medicine Department of Subulussalam General Hospital, Aceh, Indonesia. By using the total sampling method, the sample inclusion criteria were patients who were diagnosed with CHF and never consumed antidepressants before the diagnosis. Diagnosis data of CHF and its classification were obtained from clinical findings by an internist and evaluation of chest X-ray imaging with CTR>50%. The Hospital Anxiety and Depression Scale (HADS) was used in this study to show the prevalence of patients with depression and anxiety symptoms in Aceh, Indonesia. This finding might be valuable to Indonesian public policy in the context of health services.